Light Boosts the Activity of Novel LPMO from Aspergillus fumigatus Leading to Oxidative Cleavage of Cellulose and Hemicellulose - Velasco, Josman; Sepulchro, Ana Gabriela V.; Higasi, Paula M. R.; Pellegrini, Vanessa O. A.; Cannella, David; De Oliveira, Leandro Cristante [UNESP]; Polikarpov, Igor; Segato, Fernando (American Chemical Society (ACS), 2022)
Lytic polysaccharide monooxygenases (LPMOs) are copper-dependent enzymes that potentiate the deconstruction of polysaccharides through an oxidative mechanism. The oxidative catalysis of LPMOs is dependent on a reductant to promote the divalent copper ion in a metalloenzyme to its monovalent state. The reported molecules that can activate LPMOs are organic compounds of low molecular weight, enzymes, lignin and lignin-derived compounds, and, recently, photosynthetic pigments. This work reports the functional characterization and the computational modeling of the three-dimensional structure of a novel LPMO from Aspergillus fumigatus var. niveus (AfAA9C). AfAA9C shows the ability to oxidize glucose residues in the cellulose chain at C1- and C4-carbon, being the first reported LPMO from A. fumigatus active on xyloglucan and capable of being activated by light. The evaluation of electron donors coupled to chlorophyllin + light photosystems allowed to elucidate the existence of a collaborative effect between a chemical reducing agent and light-induced electron transfer systems promoting changes in LPMO activity, which is reducing agent-type-dependent. The results suggest that the preference of AfAA9C for a specific reducing agent is altered when the compound is associated with the photosystem due to H2O2generation. These findings are of general importance for the utilization of LPMOs in reactions applying photobiocatalysis and in sustainable industrial processes such as biomass depolymerization. copy; 2022 American Chemical Society.
Keywords: cellulose; lytic polysaccharide monooxygenases; photobiocatalysis; xyloglucan